Women with epilepsy in sub–Saharan Africa: A review of the reproductive health challenges and perspectives for management. (October 2019) - Menon, Sonia; Siewe Fodjo, Joseph N.; Weckhuysen, Sarah; Bhwana, Dan; Njamnshi, Alfred K.; Dekker, Marieke; Colebunders, Robert
Highlights: Data on perinatal outcomes of women with epilepsy is scarce in sub-Saharan Africa. Stigma, and poor access to healthcare worsen women with epilepsy health outcomes. Frequent contraceptive failure and teratogenicity with routine antiepileptic drugs. Urgent need for more access to less teratogenic second line anti-epileptic drugs. Abstract: Background: Epilepsy is one of the commonest neurological conditions affecting women of reproductive age. Epilepsy management during pregnancy is a clinical conundrum, requiring a balance between seizure control and risk minimization for the women with epilepsy (WWE) as well as for their fetuses. The objective of this comprehensive review is to explore the reproductive health challenges of WWE in sub-Saharan Africa (SSA) and ways to address them. Method: Relevant documentation published until June 2019 were retrieved via literature searches performed in PubMed and Google Scholar, as well as a manual search to identify grey literature. Results: WWE in SSA are generally more stigmatized and sexually exploited than women without epilepsy. Contraception use among WWE was reported only in Senegal (51%) and Kenya (14.7%). Only two prospective studies (one in Senegal and one in Nigeria) investigated pregnancy outcomes for a total of 97 WWE. The prevalence of convulsive epilepsy in pregnancy was estimated at 3.33 per 1000. Among pregnant WWE treated with first line anti-epileptic drugs, 16.2% had miscarriages, 41.9% premature births, and 4.1% had babies with malformations. Carbamazepine, which is frequently prescribed to pregnant WWE in SSA, still entails a 2.1-fold increased risk of congenital malformation. No reports were found concerning pre-conceptual counseling and post-natal outcomes in WWE in SSA. Conclusion: Our review underscores the need for contextualized evidence-based clinical guidelines and a collaborative approach to treat WWE in SSA. High risks of congenital malformations and drug interactions with first line AED warrant the provision of safer second line alternatives.